Project-Based Learning Progression: Identifying The Impact of Learning on Students' Motivation and Learning Outcomes - Arif Firmansyah; Nurul Fitriah Aras; Mardi Lestari; Muchdar Muchdar (Universitas Sebelas Maret, 2024)
The study aims to address the issue of low motivation and poor learning outcomes in Social Studies. Many students find Social Studies dull due to its focus on memorization, which leads to passive learning. Additionally, teachers' limited familiarity with various learning approaches contributes to students' lack of motivation. The study investigates whether implementing a project-based learning (PBL) model can positively impact motivation and learning outcomes in Social Studies. Fifth-grade students from SDN 17 Poso participated in the quasi-experimental research, divided into experimental and control groups. Pretests and posttests were administered before and after the learning period, respectively, to both groups. Data collection methods included tests, questionnaires, and documentation. Pretests helped establish baseline knowledge levels and facilitated comparison to evaluate the effectiveness of the PBL intervention. Results indicated a significant improvement in motivation and learning outcomes among students exposed to the project-based learning model. The study's implications extend to enhancing teaching methodologies and strategies to foster better engagement and achievement in Social Studies.